Abdominal adiposity and cardiometabolic risk factors in children and adolescents: a Mendelian randomization analysis. Issue 5 (26th August 2019) - Viitasalo, Anna; Schnurr, Theresia M; Pitkänen, Niina; Hollensted, Mette; Nielsen, Tenna R H; Pahkala, Katja; Atalay, Mustafa; Lind, Mads V; Heikkinen, Sami; Frithioff-Bøjsøe, Christine; Fonvig, Cilius E; Grarup, Niels; et al.
ABSTRACT: Background: Mendelian randomization studies in adults suggest that abdominal adiposity is causally associated with increased risk of type 2 diabetes and coronary artery disease in adults, but its causal effect on cardiometabolic risk in children remains unclear. Objective: We aimed to study the causal relation of abdominal adiposity with cardiometabolic risk factors in children by applying Mendelian randomization. Methods: We constructed a genetic risk score (GRS) using variants previously associated with waist-to-hip ratio adjusted for BMI (WHRadjBMI ) and examined its associations with cardiometabolic factors by linear regression and Mendelian randomization in a meta-analysis of 6 cohorts, including 9895 European children and adolescents aged 3–17 y. Results: WHRadjBMI GRS was associated with higher WHRadjBMI (β = 0.021 SD/allele; 95% CI: 0.016, 0.026 SD/allele; P = 3 × 10 −15 ) and with unfavorable concentrations of blood lipids (higher LDL cholesterol: β = 0.006 SD/allele; 95% CI: 0.001, 0.011 SD/allele; P = 0.025; lower HDL cholesterol: β = −0.007 SD/allele; 95% CI: −0.012, −0.002 SD/allele; P = 0.009; higher triglycerides: β = 0.007 SD/allele; 95% CI: 0.002, 0.012 SD/allele; P = 0.006). No differences were detected between prepubertal and pubertal/postpubertal children. The WHRadjBMI GRS had a stronger association with fasting insulin in children and adolescents with overweight/obesity (β = 0.016 SD/allele; 95% CI: 0.001, 0.032 SD/allele; P = 0.037) than in those with normal weight (β = −0.002 SD/allele; 95% CI: −0.010, 0.006 SD/allele; P = 0.605) ( P for difference = 0.034). In a 2-stage least-squares regression analysis, each genetically instrumented 1-SD increase in WHRadjBMI increased circulating triglycerides by 0.17 mmol/L (0.35 SD, P = 0.040), suggesting that the relation between abdominal adiposity and circulating triglycerides may be causal. Conclusions: Abdominal adiposity may have a causal, unfavorable effect on plasma triglycerides and potentially other cardiometabolic risk factors starting in childhood. The results highlight the importance of early weight management through healthy dietary habits and physically active lifestyle among children with a tendency for abdominal adiposity.